Identifying Dimensions and Components for the Enhancement of Virtual Educational Leadership in the Islamic Azad University Branches of Tehran Province Using Thematic Analysis - Jamei, Ahmad Reza; Mohammad Davoodi, Amir Hossein; Mohammadkhani, Kamran (Iranian Journal of Educational Sociology, 2022)
Purpose: The primary objective of this article is to identify the dimensions and components for the enhancement of virtual educational leadership in the Islamic Azad Universities of Tehran province using thematic analysis. Methodology: The research method employed is mixed (qualitative-quantitative). In addition to document analysis, the thematic analysis technique with MAXQDA12 software was used to identify factors and components. The study population included all faculty members with at least an assistant professorship in educational management, higher education management, and educational technology, as well as administrators of Islamic Azad Universities, with theoretical saturation achieved after 15 interviews. Ultimately, base, organizing, and comprehensive themes were extracted, and in the quantitative section, structural equation modeling was used to determine the impact and ranking of the dimensions and components. Findings: Based on semi-structured interviews, four dimensions (knowledge of educational leadership in virtual environments, performance management and coaching in virtual environments, team leadership ability in virtual environments, ethical behaviors in virtual environments) and 24 components (organizing themes) were identified for virtual educational leadership in the Islamic Azad Universities of Tehran province. Subsequently, based on a researcher-made questionnaire, it was determined that the dimension of ethical behaviors in virtual environments with a coefficient of 0.905, team leadership ability in virtual environments with a coefficient of 0.879, performance management and coaching in virtual environments with a coefficient of 0.877, and knowledge of educational leadership in virtual environments with a coefficient of 0.805 are prioritized from first to fourth, respectively. Conclusion: The findings underscore the significance of adaptability, digital proficiency, and effective communication as pivotal traits for successful virtual leaders. Notably, the study also sheds light on the potential for gender to influence leadership effectiveness in virtual environments, with female leaders possibly having an edge in fostering collaboration and inclusivity.